Retrospective Analysis of Prevalence of High-risk and Low-risk Human Papillomavirus (HPV) Genotypes in Iranian Women During 2013-2016 - Chalabiani, Siavash; Khodadad Nazari, Mina; Shabani, Mahdi; Razavi Davoodi, Neda; Sarafnejad, Abdolfattah; Amirzargar, Ali Akbar (Asian Pacific Journal of Cancer Biology, 2017)
Background and objective: Considering the importance of HPV in cancer etiology, awareness of HPV prevalence and frequency of high-risk genotypes could help improve health care system management. We analyzed HPV prevalence in women forms different provinces of Iran that is the largest sample till now. Material and Methods: In this retrospective cross-sectional study, 2969 outpatient and suspicious women aged 17- 78 referred to Noor pathobiology laboratory from 24 provinces of Iran were studies. DNA extraction and PCR were performed on samples and then HPV genotypes were also determined using hybridization kit. Results: HPV DNA was detected in 29.3% of valid liquid-based samples. Among HPV positive cases, 67.2% and 52.0% accounted for high-risk and low-risk HPV subtypes, respectively. In patients with high-risk HPV types, HPV16 was confirmed as predominate type (30.5%) followed by HPV53 (17.3%) and HPV39 (13.3 %). HPV6 was found as the most common low-risk HPV type with 60.6% frequency rate followed by HPV11 (17.9%) and HPV81 (8.6%) in this age group. It was apparent that age group >25 years accounted the highest frequency of HPV positivity. The prevalence of HPV was significantly different among different age groups (p<0.0001). Conclusion: It can be concluded that HPV infection is currently at a considerable high level in Iran. Looking at the high risk and oncogenic HPV subtypes frequency especially in younger age groups, a concern could be noticed about HPV relevant cancers which can be prevented by commercial and approved HPV vaccines.